2022
DOI: 10.1002/hep4.2099
|View full text |Cite
|
Sign up to set email alerts
|

Glycine‐β‐muricholic acid antagonizes the intestinal farnesoid X receptor–ceramide axis and ameliorates NASH in mice

Abstract: Nonalcoholic steatohepatitis (NASH) is a rapidly developing pathology around the world, with limited treatment options available. Some farnesoid X receptor (FXR) agonists have been applied in clinical trials for NASH, but side effects such as pruritus and low‐density lipoprotein elevation have been reported. Intestinal FXR is recognized as a promising therapeutic target for metabolic diseases. Glycine‐β‐muricholic acid (Gly‐MCA) is an intestine‐specific FXR antagonist previously shown to have favorable metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
(71 reference statements)
0
0
0
Order By: Relevance
“…Reduced lipid accumulation, inflammatory response (in injury markers, ALT and AST), and collagen deposition in NAFLD and NASH models. Lower liver endoplasmic reticulum stress and proinflammatory cytokine production (97).…”
Section: Fxr Agonistsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced lipid accumulation, inflammatory response (in injury markers, ALT and AST), and collagen deposition in NAFLD and NASH models. Lower liver endoplasmic reticulum stress and proinflammatory cytokine production (97).…”
Section: Fxr Agonistsmentioning
confidence: 99%
“…Improved MASLD was explained by a decreased de novo lipogenesis in treated mice ( 118 ). Glycine-β-muricholic acid (Gly-MCA) is an FXR agonist that suppresses ceramide synthesis-related genes, thus reducing ceramide levels in the livers of treated mice ( 97 ). A generally improved inflammatory response was seen in both MASLD and MASH mice models treated with this agonist, which showed fewer injury markers and lower levels of aspartate and alanine transaminases ( 97 ).…”
Section: Experimental/clinical Evidence Of Therapies Targeting Sphing...mentioning
confidence: 99%
See 1 more Smart Citation
“…We have summarized the hypoglycemic mechanisms and glucose outcomes of bile acid-related drugs, as shown in Table 1. In these studies, BAs (CDCA [42,43], TUDCA [31,44,45], HCA [46], GUDCA [47]), FXR inhibitors (HS218 [48], Gly-MCA [49,50]), FXR agonists (Fexaramine [51,52], GW4064 [53,54]), FXR/TGR5 agonists (INT-767 [55]), TGR5 agonists (INT-777 [52], RO5527239 [52]), and clinical drugs (Colesevelam [56], Metformin [37,57,58], Acarbose [41], Obeticholic acid (OCA) [59][60][61]) all demonstrated hypoglycemic effects by activating different mechanisms. However, one study found that blood glucose increased in mice treated with GW4064 [62].…”
Section: Bile Acids and Diabetes Drugs (Metformin And Acarbose)mentioning
confidence: 99%
“…Bile acids can be agonists or antagonists of FXR in a structureand concentration-dependent manner [15][16][17][18]. For instance, the main species comprising 40% of the total bile acid pool in humans, chenodeoxycholic acid (DCA), is a FXR agonist, while the main family of bile acids in mice, muricholic acids (MCAs), are generally FXR antagonists [18,19]. The activation of FXR limits intracellular bile acid levels and overall results in bile acid elimination [20].…”
Section: Introductionmentioning
confidence: 99%